Climate Change Education in Formal Settings, K-14: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Climate change is occurring, is very likely caused by human activities, and poses significant risks for a broad range of human and natural systems. Each additional ton of greenhouse gases emitted commits us to further change and greater risks. In the judgment of the Committee on America's Climate Choices, the environmental, economic, and humanitarian risks of climate change indicate a pressing need for substantial action to limit the magnitude of climate change and to prepare to adapt to its impacts. A principal message from the recent National Research Council report, America's Climate Choices, this brief summary of how climate change will shape many aspects of life in the foreseeable future emphasizes the vital importance of preparation for these changes. The report points to the importance of formal and informal education in supporting the public's understanding of those challenges climate change will bring, and in preparing current and future generations to act to limit the magnitude of climate change and respond to those challenges. Recognizing both the urgency and the difficulty of climate change education, the National Research Council, with support from the National Science Foundation, formed the Climate Change Education Roundtable. The roundtable brings together federal agency representatives with diverse experts and practitioners in the physical and natural sciences, social sciences, learning sciences, environmental education, education policy, extension education and outreach, resource management, and public policy to engage in discussion and explore educational strategies for addressing climate change. Two workshops were held to survey the landscape of climate change education. The first explored the goals for climate change education for various target audiences. The second workshop, which is the focus of this summary, was held on August 31 and September 1, 2011, and focused on the teaching and learning of climate change and climate science in formal education settings, from kindergarten through the first two years of college (K-14). This workshop, based on an already articulated need to teach climate change education, provided a forum for discussion of the evidence from research and practice. The goal of this workshop was to raise and explore complex questions around climate change education, and to address the current status of climate change education in grade K-14 of the formal education system by facilitating discussion between expert researchers and practitioners in complementary fields, such as education policy, teacher professional development, learning and cognitive science, K-12 and higher education administration, instructional design, curriculum development, and climate science. Climate Change Education in Formal Settings, K-14: A Workshop Summary summarizes the two workshops.

Key National Education Indicators: Workshop Summary - National Research Council (The National Academies Press, 2012)
The education system in the United States is continually challenged to adapt and improve, in part because its mission has become far more ambitious than it once was. At the turn of the 20th century, less than one-tenth of students enrolled were expected to graduate from high school. Today, most people expect schools to prepare all students to succeed in postsecondary education and to prosper in a complex, fast-changing global economy. Goals have broadened to include not only rigorous benchmarks in core academic subjects, but also technological literacy and the subtler capacities known as 21st-century skills. To identify the most important measures for education and other issues and provide quality data on them to the American people, Congress authorized the creation of a Key National Indicators System (KNIS). This system will be a single Web-based information source designed to help policy makers and the public better assess the position and progress of the nation across a wide range of areas. Identifying the right set of indicators for each area is not a small challenge. To serve their purpose of providing objective information that can encourage improvement and innovation, the indicators need to be valid and reliable but they also need to capture the report committee's aspirations for education. This report describes a workshop, planned under the aegis of the Board on Testing and Assessment and the Committee on National Statistics of the National Research Council. Key National Education Indicators is a summary of the meeting of a group with extensive experience in research, public policy, and practice. The goal of the workshop was not to make a final selection of indicators, but to take an important first step by clearly identifying the parameters of the challenge.

Challenges in Chemistry Graduate Education: A Workshop Summary - National Research Council
Chemistry graduate education is under considerable pressure. Pharmaceutical companies, long a major employer of synthetic organic chemists, are drastically paring back their research divisions to reduce costs. Chemical companies are opening new research and development facilities in Asia rather than in the United States to take advantage of growing markets and trained workforces there. Universities, especially public universities, are under significant fiscal constraints that threaten their ability to hire new faculty members. Future federal funding of chemical research may be limited as the federal budget tightens. All of these trends have major consequences for the education of chemistry graduate students in U.S. universities. To explore and respond to these intensifying pressures, the Board on Chemical Sciences and Technology held a workshop in Washington, DC, on January 23-24 2012, titled \

Himalayan Glaciers: Climate Change, Water Resources, and Water Security - National Research Council (The National Academies Press, 2012)
Scientific evidence shows that most glaciers in South Asia's Hindu Kush Himalayan region are retreating, but the consequences for the region's water supply are unclear, this report finds. The Hindu Kush Himalayan region is the location of several of Asia's great river systems, which provide water for drinking, irrigation, and other uses for about 1.5 billion people. Recent studies show that at lower elevations, glacial retreat is unlikely to cause significant changes in water availability over the next several decades, but other factors, including groundwater depletion and increasing human water use, could have a greater impact. Higher elevation areas could experience altered water flow in some river basins if current rates of glacial retreat continue, but shifts in the location, intensity, and variability of rain and snow due to climate change will likely have a greater impact on regional water supplies. Himalayan Glaciers: Climate Change, Water Resources, and Water Security makes recommendations and sets guidelines for the future of climate change and water security in the Himalayan Region. This report emphasizes that social changes, such as changing patterns of water use and water management decisions, are likely to have at least as much of an impact on water demand as environmental factors do on water supply. Water scarcity will likely affect the rural and urban poor most severely, as these groups have the least capacity to move to new locations as needed. It is predicted that the region will become increasingly urbanized as cities expand to absorb migrants in search of economic opportunities. As living standards and populations rise, water use will likely increase-for example, as more people have diets rich in meat, more water will be needed for agricultural use. The effects of future climate change could further exacerbate water stress. Himalayan Glaciers: Climate Change, Water Resources, and Water Security explains that changes in the availability of water resources could play an increasing role in political tensions, especially if existing water management institutions do not better account for the social, economic, and ecological complexities of the region. To effectively respond to the effects of climate change, water management systems will need to take into account the social, economic, and ecological complexities of the region. This means it will be important to expand research and monitoring programs to gather more detailed, consistent, and accurate data on demographics, water supply, demand, and scarcity.

Climate Change: Evidence, Impacts, and Choices: Set of 3 Booklets - National Research Council (The National Academies Press, 2012)
What is climate? Climate is commonly thought of as the expected weather conditions at a given location over time. People know when they go to New York City in winter, they should take a heavy coat. When they visit the Pacific Northwest, they should take an umbrella. Climate can be measured as many geographic scales - for example, cities, countries, or the entire globe - by such statistics as average temperatures, average number of rainy days, and the frequency of droughts. Climate change refers to changes in these statistics over years, decades, or even centuries. Enormous progress has been made in increasing our understanding of climate change and its causes, and a clearer picture of current and future impacts is emerging. Research is also shedding light on actions that might be taken to limit the magnitude of climate change and adapt to its impacts. Climate Change: Evidence, Impacts, and Choices is intended to help people understand what is known about climate change. First, it lays out the evidence that human activities, especially the burning of fossil fuels, are responsible for much of the warming and related changes being observed around the world. Second, it summarizes projections of future climate changes and impacts expected in this century and beyond. Finally, the booklet examines how science can help inform choice about managing and reducing the risks posed by climate change. The information is based on a number of National Research Council reports, each of which represents the consensus of experts who have reviewed hundreds of studies describing many years of accumulating evidence.

Climate Change: Evidence, Impacts, and Choices: PDF Booklet - National Research Council (The National Academies Press, 2012)
What is climate? Climate is commonly thought of as the expected weather conditions at a given location over time. People know when they go to New York City in winter, they should take a heavy coat. When they visit the Pacific Northwest, they should take an umbrella. Climate can be measured as many geographic scales - for example, cities, countries, or the entire globe - by such statistics as average temperatures, average number of rainy days, and the frequency of droughts. Climate change refers to changes in these statistics over years, decades, or even centuries. Enormous progress has been made in increasing our understanding of climate change and its causes, and a clearer picture of current and future impacts is emerging. Research is also shedding light on actions that might be taken to limit the magnitude of climate change and adapt to its impacts. Climate Change: Evidence, Impacts, and Choices is intended to help people understand what is known about climate change. First, it lays out the evidence that human activities, especially the burning of fossil fuels, are responsible for much of the warming and related changes being observed around the world. Second, it summarizes projections of future climate changes and impacts expected in this century and beyond. Finally, the booklet examines how science can help inform choice about managing and reducing the risks posed by climate change. The information is based on a number of National Research Council reports, each of which represents the consensus of experts who have reviewed hundreds of studies describing many years of accumulating evidence.

Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The National Research Council (NRC) and National Academy of Engineering (NAE) have released a new report, Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit. Based on a national summit that was supported by the National Science Foundation and organized by the NRC and the NAE, the report highlights the importance of community colleges, especially in emerging areas of STEM (Sciene, Technology, Engineering, and Mathematics) and preparation of the STEM workforce. Community colleges are also essential in accommodating growing numbers of students and in retraining displaced workers in skills needed in the new economy. Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit looks at the changing and evolving relationships between community colleges and four-year institutions, with a focus on partnerships and articulation processes that can facilitate student success in STEM; expanding participation of students from historically underrepresented populations in undergraduate STEM education; and how subjects, such as mathematics, can serve as gateways or barriers to college completion.

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field. A Framework for K-12 Science Education outlines a broad set of expectations for students in science and engineering in grades K-12. These expectations will inform the development of new standards for K-12 science education and, subsequently, revisions to curriculum, instruction, assessment, and professional development for educators. This book identifies three dimensions that convey the core ideas and practices around which science and engineering education in these grades should be built. These three dimensions are: crosscutting concepts that unify the study of science through their common application across science and engineering; scientific and engineering practices; and disciplinary core ideas in the physical sciences, life sciences, and earth and space sciences and for engineering, technology, and the applications of science. The overarching goal is for all high school graduates to have sufficient knowledge of science and engineering to engage in public discussions on science-related issues, be careful consumers of scientific and technical information, and enter the careers of their choice. A Framework for K-12 Science Education is the first step in a process that can inform state-level decisions and achieve a research-grounded basis for improving science instruction and learning across the country. The book will guide standards developers, teachers, curriculum designers, assessment developers, state and district science administrators, and educators who teach science in informal environments.

Summary of a Workshop on the Future of Antennas - National Research Council (The National Academies Press, 2012)
The Workshop on the Future of Antennas was the second of three workshops conducted by the National Research Council's Committee for Science and Technology Challenges to U.S. National Security Interests. The objectives of the workshop were to review trends in advanced antenna research and design, review trends in commercials and military use of advanced antennas that enable improved communication, data transfer, soldier health monitoring, and other overt and covert methods of standoff data collection. The first day's sessions, consisting of five presentations and discussions on antennas and wireless communications and control, were open to committee members, staff, guests, and members of the public. The second day was a data-gathering session addressing vulnerabilities, indicators, and observables; presentations and discussions during this session included classified material and were not open to the public. The committee's role was limited to planning and convening the workshop. This report is organized by topic in the order of presentation and discussion at the workshop. For Day 1 the topics were Future of Antennas, Commercial State of the Art of Wireless Communications and Control, Military State of the Art of Wireless Communications and Control, and Future Trends in Antenna Design and Wireless Communications and Control. For Day 2 the topics were Vulnerabilities of Ubiquitous Antennas, and Indicators and Observables, followed by a wrap-up discussion. Summary of a Workshop on the Future of Antennas describes what happened at the workshop.

Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation - National Research Council (The National Academies Press, 2012)
Evolution is the central unifying theme of biology. Yet today, more than a century and a half after Charles Darwin proposed the idea of evolution through natural selection, the topic is often relegated to a handful of chapters in textbooks and a few class sessions in introductory biology courses, if covered at all. In recent years, a movement has been gaining momentum that is aimed at radically changing this situation. On October 25-26, 2011, the Board on Life Sciences of the National Research Council and the National Academy of Sciences held a national convocation in Washington, DC, to explore the many issues associated with teaching evolution across the curriculum. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation summarizes the goals, presentations, and discussions of the convocation. The goals were to articulate issues, showcase resources that are currently available or under development, and begin to develop a strategic plan for engaging all of the sectors represented at the convocation in future work to make evolution a central focus of all courses in the life sciences, and especially into introductory biology courses at the college and high school levels, though participants also discussed learning in earlier grades and life-long learning. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation covers the broader issues associated with learning about the nature, processes, and limits of science, since understanding evolutionary science requires a more general appreciation of how science works. This report explains the major themes that recurred throughout the convocation, including the structure and content of curricula, the processes of teaching and learning about evolution, the tensions that can arise in the classroom, and the target audiences for evolution education.

From Neurons to Neighborhoods: An Update: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2012)
From Neurons to Neighborhoods: An Update: Workshop Summary is based on the original study From Neurons to Neighborhoods: Early Childhood Development, which released in October of 2000. From the time of the original publication's release, much has occurred to cause a fundamental reexamination of the nation's response to the needs of young children and families, drawing upon a wealth of scientific knowledge that has emerged in recent decades. The study shaped policy agendas and intervention efforts at national, state, and local levels. It captured a gratifying level of attention in the United States and around the world and has helped to foster a highly dynamic and increasingly visible science of early childhood development. It contributed to a growing public understanding of the foundational importance of the early childhood years and has stimulated a global conversation about the unmet needs of millions of young children. Ten years later, the Board on Children, Youth, and Families of the Institute of Medicine (IOM) and the National Research Council (NRC) held a 2-day workshop in Washington, D.C., to review and commemorate a decade of advances related to the mission of the report. The workshop began with a series of highly interactive breakout sessions in which experts in early childhood development examined the four organizing themes of the original report and identified both measurable progress and remaining challenges. The second day of the workshop, speakers chosen for their diverse perspectives on early childhood research and policy issues discussed how to build on the accomplishments of the past decade and to launch the next era in early childhood science, policy, and practice. From Neurons to Neighborhoods: An Update: Workshop Summary emphasizes that there is a single, integrated science of early childhood development despite the extent to which it is carved up and divided among a diversity of professional disciplines, policy sectors, and service delivery systems. While much work still remains to be done to reach this goal, the 2010 workshop demonstrated both the promise of this integrated science and the rich diversity of contributions to that science.

Informatics Needs and Challenges in Cancer Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
As information technology becomes an integral part of health care, it is important to collect and analyze data in a way that makes the information understandable and useful. Informatics tools2014which help collect, organize, and analyze data2014are essential to biomedical and health research and development. The field of cancer research is facing an overwhelming deluge of data, heightening the national urgency to find solutions to support and sustain the cancer informatics ecosystem. There is a particular need to integrate research and clinical data to facilitate personalized medicine approaches to cancer prevention and treatment2014for example, tailoring treatment based on an individual patient's genetic makeup as well as that of the tumor2014and to allow for more rapid learning from patient experiences. To further examine informatics needs and challenges for 21st century biomedical research, the IOM's National Cancer Policy Forum held a workshop February 27-28, 2012. The workshop was designed to raise awareness of the critical and urgent importance of the challenges, gaps and opportunities in informatics; to frame the issues surrounding the development of an integrated system of cancer informatics for acceleration of research; and to discuss solutions for transformation of the cancer informatics enterprise. Informatics Needs and Challenges in Cancer Research: Workshop Summary summarizes the workshop.

The Effects of Solar Variability on Earth's Climate: A Workshop Report - National Research Council (The National Academies Press, 2012)
On September 8-9, 2011, experts in solar physics, climate models, paleoclimatology, and atmospheric science assembled at the National Center for Atmospheric Research (NCAR) in Boulder, Colorado for a workshop to consider the Sun's variability over time and potential Sun-climate connections.While it does not provide findings, recommendations, or consensus on the current state of the science, The Effects of Solar Variability on Earth's Climate: A Workshop Report briefly introduces the primary topics discussed by presenters at the event. As context for these topics, the summary includes background information on the potential Sun-climate connection, the measurement record from space, and potential perturbations of climate due to long-term solar variability. This workshop report also summarizes some of the science questions explored by the participants as potential future research endeavors.

The Early Childhood Care and Education Workforce: Challenges and Opportunities: A Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2012)
Early childhood care and education (ECCE) settings offer an opportunity to provide children with a solid beginning in all areas of their development. The quality and efficacy of these settings depend largely on the individuals within the ECCE workforce. Policy makers need a complete picture of ECCE teachers and caregivers in order to tackle the persistent challenges facing this workforce. The IOM and the National Research Council hosted a workshop to describe the ECCE workforce and outline its parameters. Speakers explored issues in defining and describing the workforce, the marketplace of ECCE, the effects of the workforce on children, the contextual factors that shape the workforce, and opportunities for strengthening ECCE as a profession.

The Continuing Epidemiological Transition in Sub-Saharan Africa: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Among the poorest and least developed regions in the world, sub-Saharan Africa has long faced a heavy burden of disease, with malaria, tuberculosis, and, more recently, HIV being among the most prominent contributors to that burden. Yet in most parts of Africa-and especially in those areas with the greatest health care needs-the data available to health planners to better understand and address these problems are extremely limited. The vast majority of Africans are born and will die without being recorded in any document or spearing in official statistics. With few exceptions, African countries have no civil registration systems in place and hence are unable to continuously generate vital statistics or to provide systematic information on patterns of cause of death, relying instead on periodic household-level surveys or intense and continuous monitoring of small demographic surveillance sites to provide a partial epidemiological and demographic profile of the population. In 1991 the Committee on Population of the National Academy of Sciences organized a workshop on the epidemiological transition in developing countries. The workshop brought together medical experts, epidemiologists, demographers, and other social scientists involved in research on the epidemiological transition in developing countries to discuss the nature of the ongoing transition, identify the most important contributors to the overall burden of disease, and discuss how such information could be used to assist policy makers in those countries to establish priorities with respect to the prevention and management of the main causes of ill health. This report summarizes the presentations and discussions from a workshop convened in October 2011 that featured invited speakers on the topic of epidemiological transition in sub-Saharan Africa. The workshop was organized by a National Research Council panel of experts in various aspects of the study of epidemiological transition and of sub-Saharan data sources. The Continuing Epidemiological Transition in Sub-Saharan Africa serves as a factual summary of what occurred at the workshop in October 2011.

Rising Above the Gathering Storm: Developing Regional Innovation Environments: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In October 2005, the National Academy of Sciences, National Academy of Engineering, and Institute of Medicine released a policy report that served as a call to action. The report, Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future observed that \

Genome-Based Diagnostics: Clarifying Pathways to Clinical Use: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The sequencing of the human genome and the identification of associations between specific genetic variants and diseases have led to an explosion of genomic-based diagnostic tests. These tests have the potential to direct therapeutic interventions, predict risk or onset of disease, or detect residual disease. As research progresses and an increasing number of associations are found, further tests will be developed that can aid in providing personalized treatment options for patients. However, the adoption of genomic diagnostic tests by health care providers has been limited due to a lack of evidence regarding the clinical utility of many tests. Health funders and practitioners lack the data necessary to distinguish which tests can improve practice or the clinical settings in which tests will provide the greatest value. The Roundtable on Translating Genomic-Based Research for Health held a workshop in November 2010 to determine what evidence is needed and how it is viewed by different stakeholders in order to develop genomic diagnostic tests of clinical value. Genome-Based Diagnostics summarizes the presentations and discussions that took place throughout the workshop. Two presentations, in particular, sparked extensive discussion. One presentation proposed that all genomic diagnostic tests be reviewed and approved by the Food and Drug Administration. The other observed that venture capitalists are no longer investing substantially in the development of genomic diagnostic tests because of a lack of clarity surrounding regulatory and reimbursement pathways. Both presentations suggested the need for major changes in the systems used to develop, regulate, and reimburse genomic diagnostic tests. The report also presents the perspectives of different stakeholders in the development of genomic diagnostic tests. Each stakeholder group has a different set of needs and issues of importance, yet commonalities among them are apparent, such as the need to put patients and health outcomes at the center of discussion and action.

Nutrition and Healthy Aging in the Community: Workshop Summary - Institute of Medicine
The U.S. population of older adults is predicted to grow rapidly as \

Child Maltreatment Research, Policy, and Practice for the Next Decade: Workshop Summary - Institute of Medicine; National Research Council
In 1993 the National Research Council released its landmark report Understanding Child Abuse and Neglect (NRC, 1993). That report identified child maltreatment as a devastating social problem in American society. Nearly 20 years later, on January 30-31, 2012, the Institute of Medicine (IOM) and NRC's Board on Children, Youth and Families help a workshop, Child Maltreatment Research, Policy, and Practice for the Next Generation, to review the accomplishments of the past two decades of research related to child maltreatment and the remaining gaps. \

Sex-Specific Reporting of Scientific Research: A Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
The number of women participating in clinical trials has increased during the last two decades, but women are still underrepresented in clinical trials in general. Some of the overall increase can be attributed to the greater number of women-only trials (of therapies for diseases that affect only women). Even when women are included in clinical trials, the results are often not analyzed separately by sex. On August 30, 2011, the Institute of Medicine (IOM) Board on Population Health and Public Health Practice hosted the workshop Sex-Specific Reporting of Scientific Research. The workshop explored the need for sex-specific reporting of scientific results; potential barriers and unintended consequences of sex-specific reporting of scientific results; experiences of journals that have implemented sex-specific requirements, including the challenges and benefits of such editorial policies; and steps to facilitate the reporting of sex-specific results. Presenters and participants included current and former editors of scientific journals, researchers, and scientists and policymakers from government, industry, and nonprofit organizations. Presentations and discussions highlighted the importance to both women and men of having sex-specific data, the problems with sample size and financial constraints for conducting the research, the appropriateness of sex-specific analyses, and the limitations of journal policies to change experimental designs. Sex-Specific Reporting of Scientific Research summarizes the presentations and discussions by the expert panelists during the IOM workshop. The workshop's first session focused on why sex-specific reporting is important. Panelists highlighted historical and current events that have hindered or helped to advance the study of women. In the next session, panelists in academe discussed the challenges of collecting, analyzing, and reporting sex-specific data from the researcher's perspective. That was followed by two panels of leading journal editors who shared their experiences in developing and implementing editorial policies and the implications of sex-specific reporting policies for journals.